Membentuk Karakter Melalui Seni Pertunjukan: Analisis Penanaman Nilai Karakter dalam Drama Musikal Randai Rantau Malin oleh Grup Palito Nyalo - Djulian Anggara; Widodo; Slamet Haryono (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2023)
Purpose: This study aims to explain the values of character education contained in the musical drama performance Randai Rantau Malin performed by the Palito Nyalo art group in Pauh District, Padang City. The current character crisis has made an alarming impact on the life of the nation and state. The rise of technological developments today has a negative influence on the younger generation. The government began to emphasize strengthening character education in every educational institution, both formal education and non-formal education, one of which was by providing traditional art training. Method: This research uses qualitative methods with data collection methods taken through observation, interviews, literature studies, and documentation. Data analysis uses qualitative descriptive methods obtained from primary and secondary data. Result and Discussion: The results of this study show that children who participate in learning and engaging in the musical drama performance Randai Rantau Malin better understand the values of character and instill these values in their daily lives. They realize character values such as religious values, honesty values, tolerance values, discipline, creativity, and gotong-royong values. In the event of Rantau Malin, many values and messages can be learned, because the initial function of this art itself is not only as entertainment but there are many elements of values and messages for daily life that can be realized in the family and community. By itself, the values contained in this art can shape the character of today's young generation.